Analisis Penerapan Konsep Mitigasi Tsunami pada Hardscape Taman Kota (Studi Kasus: Taman Krueng Neng) - Harya Frida; Meutia; Era Nopera Rauzi (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Krueng Neng Park is one of the city parks in Banda Aceh which is located on the banks of the Kampong Lamjame river, Jaya Baru District, Banda Aceh. This park with an area of 1.52 ha is one part of the Green Open Space (RTH) development. its location on the banks of the Surin River is the main attraction of this park. Krueng Neng Park is one of the parks that was affected by the tsunami wave in 2004. Due to its location in an area designated as a tsunami mitigation-based area, Krueng Neng Park needs to apply the concept of tsunami mitigation. The existence of the Krueng Neng park raises questions for researchers, especially regarding the hardscape application of the tsunami mitigation concept that exists in the Krueng Neng park, based on the applicable standardization principles. With the aim of analyzing the application of the existing tsunami mitigation concept to the Krueng Neng park, and recommending an appropriate tsunami mitigation concept to the Krueng Neng park.